2006
DOI: 10.2460/ajvr.67.3.479
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gastrointestinal permeability and mucosal absorptive capacity in dogs with chronic enteropathy

Abstract: Results of tests for intestinal permeability and mucosal absorptive capacity were not useful indicators of clinical disease activity as assessed by the CIBDAI or the sever ity of infiltration as indicated by histologic evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 30 publications
3
23
3
Order By: Relevance
“…These results indicate that intestinal permeability tests such as the urinary L:R ratio are useful for assessing mucosal damage in LPE dogs. Recently, Allenspach et al reported that gastrointestinal permeability does not increase in dogs with chronic enteropathy (CE) and that there is no significant difference in permeability before and after treatment [1]. This is not in agreement with our results; one possible explanation for this discrepancy is the severity of the selected cases.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…These results indicate that intestinal permeability tests such as the urinary L:R ratio are useful for assessing mucosal damage in LPE dogs. Recently, Allenspach et al reported that gastrointestinal permeability does not increase in dogs with chronic enteropathy (CE) and that there is no significant difference in permeability before and after treatment [1]. This is not in agreement with our results; one possible explanation for this discrepancy is the severity of the selected cases.…”
Section: Discussioncontrasting
confidence: 57%
“…It has been reported to show good correlation with histological scoring. However, our results as well as those of previous studies demonstrate the absence of any correlation between histological evaluation and CIB-DAI in IBD dogs [1,12]. This suggests that clinical scoring systems such as CIBDAI do not always reflect the severity of intestinal damage, especially in cases of severe IBD.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In particular, patients with Crohn's disease (CD) and 10-20% of their clinically unaffected relatives have been shown to have increased intestinal permeability, implicating altered intestinal permeability in the pathogenesis of IBD (Hollander et al 1986;Katz et al 1989). Similarly, heightened paracellular permeability, as demonstrated by measurement of lactulose-to-rhamnose ratios (Quigg et al 1993;Allenspach et al 2006) and by measurement of transepithelial electrical resistance (Ulrich et al 2004), has been demonstrated in some dogs with chronic idiopathic enteropathy (lymphocytic-plasmacytic enteritis and/or colitis) and idiopathic IBD, respectively.…”
mentioning
confidence: 99%